(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
In Chile, the beginning of the work of the Consejo Constitucional – the conservative-majority body that will draft within four months a new constitution that should replace the existing 1980 Constitution – serves to outline the ongoing constitution-making process. This can be done considering the first year of the presidency of progressive Gabriel Boric, who was its promoter but will not be able to lead it. Instead, it will be led by the ultra-conservative José Antonio Kast, leader of the Partido Republicano de Chile, which has always declared itself opposed to a reform of the Fundamental Charter and which holds precisely the majority in the Consejo Constitucional.